A rare case of juvenile pleomorphic adenoma of buccal salivary glands. - Akhtar, M.U.; Ali, K.; Amjad, M. (European Journal of Pediatric Dermatology, 2012)
Salivary gland neoplasms are rare in children. Pleomorphic adenoma is the commonest salivary gland tumor in childhood as in adults and the majority of cases are known to involve the parotid gland. We report a rare case of pleomorphic adenoma of the buccal salivary glands in a 6-year-old female child.